2013
DOI: 10.1124/mol.112.084319
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Nerve Terminal Mitochondrial Dysfunction Activates Airway Sensory Nerves via Transient Receptor Potential (TRP) Channels

Abstract: Mitochondrial dysfunction and subsequent oxidative stress has been reported for a variety of cell types in inflammatory diseases. Given the abundance of mitochondria at the peripheral terminals of sensory nerves and the sensitivity of transient receptor potential (TRP) ankyrin 1 (A1) and TRP vanilloid 1 (V1) to reactive oxygen species (ROS) and their downstream products of lipid peroxidation, we investigated the effect of nerve terminal mitochondrial dysfunction on airway sensory nerve excitability. Here we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 59 publications
(133 reference statements)
9
63
0
Order By: Relevance
“…1A). Antimycin A (20 mM) evoked significant action potential discharge in TRPA1-expressing bronchopulmonary fibers via a ROS-dependent TRPA1 activation-this mechanism is described in our previous study (Nesuashvili et al, 2013). The direct activation of these TRPA1-expressing nerves lasted from 2 to 7 minutes; other fibers were not overtly activated.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…1A). Antimycin A (20 mM) evoked significant action potential discharge in TRPA1-expressing bronchopulmonary fibers via a ROS-dependent TRPA1 activation-this mechanism is described in our previous study (Nesuashvili et al, 2013). The direct activation of these TRPA1-expressing nerves lasted from 2 to 7 minutes; other fibers were not overtly activated.…”
Section: Resultsmentioning
confidence: 88%
“…In this preparation, the action potential discharge evoked in individual nerves by either mechanical or chemical stimuli to the airways can be quantified. Previous studies have shown that the majority of fibers innervating the lung are slowly conducting and express TRPA1 and TRPV1 (Nassenstein et al, 2008;Nesuashvili et al, 2013). This subset of nerves is thought to serve as nociceptors in the mouse airways.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations